Anaerobic membrane bioreactors for pharmaceutical-laden wastewater treatment: A critical review. (October 2022) - Oberoi, Akashdeep Singh; Surendra, K.C.; Wu, Di; Lu, Hui; Wong, Jonathan W.C.; Kumar Khanal, Samir
Graphical abstract: Highlights: Fate and removal of diverse pharmaceuticals in AnMBR system are critically reviewed. Potential role of different AD stages in pharmaceuticals biotransformation is elucidated. Key microbial communities in conjunction with pharmaceuticals removal are unraveled. Membrane biofouling layer play a positive role in pharmaceuticals removal. Advances in AnMBR configurations for mitigating biofouling are critically discussed. Abstract: Pharmaceuticals are a diverse group of chemical compounds widely used for prevention and treatment of infectious diseases in both humans and animals. Pharmaceuticals, either in their original or metabolite form, find way into the wastewater treatment plants (WWTPs) from different sources. Recently, anaerobic membrane bioreactors (AnMBR) has received significant research attention for the treatment of pharmaceuticals in various wastewater streams. This review critically examines the behaviour and removal of a wide array of pharmaceuticals in AnMBR with primary focus on their removal efficiencies and mechanisms, critical influencing factors, and the microbial community structures. Subsequently, the inhibitory effects of pharmaceuticals on the performance of AnMBR and membrane fouling are critically discussed. Furthermore, the imperative role of membrane biofouling layer and its components in pharmaceuticals removal is highlighted. Finally, recent advancements in AnMBR configurations for membrane fouling control and enhanced pharmaceuticals removal are systemically discussed.